Corrosion behaviour of super ferritic stainless steel 020Cr25MoCuNbTi in the waste phosphoric acid of a surface treatment process. (March 2023) - Ouyang, Minghui; Pan, Jie; Cai, Faming; Wang, Chundong; Liu, Huan-an; Li, Jun; Xiao, Xueshan
Abstract: The corrosion behaviour of super ferritic stainless steel 020Cr25MoCuNbTi in waste phosphoric acid during the surface treatment process was investigated between 25 and 80 ℃. After 24 h of immersion, 020Cr25MoCuNbTi is found to be spontaneously passivated at all temperatures. The corrosion resistance increases with immersion time and decreases with temperature. The passive film is mainly composed of chromium oxide and hydroxide in addition to phosphates or polyphosphates. The super ferritic stainless steel 020Cr25MoCuNbTi is revealed to show excellent resistance to waste phosphoric acid corrosion. Graphical Abstract: ga1 Highlights: 020Cr25MoCuNbTi shows excellent corrosion resistance to waste phosphoric acid. The passive film is composed of Cr2 O3 and Cr(OH)3 besides phosphates or polyphosphates. The increase in solubility or rate of ion transport with temperature causes the degradation of the passive film.